2014
DOI: 10.3389/fimmu.2014.00132
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Pre-Clustering and T cell Responses: Insights into Molecular Mechanisms

Abstract: T cell activation, initiated by T cell receptor (TCR) mediated recognition of pathogen-derived peptides presented by major histocompatibility complex class I or II molecules (pMHC), shows exquisite specificity and sensitivity, even though the TCR–pMHC binding interaction is of low affinity. Recent experimental work suggests that TCR pre-clustering may be a mechanism via which T cells can achieve such high sensitivity. The unresolved stoichiometry of the TCR makes TCR–pMHC binding and TCR triggering, an open qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 71 publications
(117 reference statements)
0
29
0
Order By: Relevance
“…Indeed, there is evidence for fast motion of microvilli following interaction with model surfaces (50). Furthermore, the concentration of TCRs on a relatively small area of highly exposed cell projections might significantly increase the avidity of these receptors to peptide-MHC complexes on APC surfaces (45,51). Finally, these actin-enriched projections may also serve as physical barriers for the diffusion and random mixing of nonmicrovillar surface proteins with microvillar proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence for fast motion of microvilli following interaction with model surfaces (50). Furthermore, the concentration of TCRs on a relatively small area of highly exposed cell projections might significantly increase the avidity of these receptors to peptide-MHC complexes on APC surfaces (45,51). Finally, these actin-enriched projections may also serve as physical barriers for the diffusion and random mixing of nonmicrovillar surface proteins with microvillar proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To define the differences between OT-II WT and CCR5 -/cells, we used a model that accounts for receptor clustering dynamics (Castro et al, 2014), a Bayesian inference method that estimates the so-called clustering parameter, b. Based on this model, we concluded that the probability of a chance nanocluster distribution similar to that observed for naïve and activated OT-II WT and CCR5 -/cells approaches 0% (Fig.…”
Section: Ccr5 Modulates Tcr Nanoclustering In Antigen-experienced Cd4mentioning
confidence: 99%
“…To quantify the mechanistic relevance of cluster size between random distributions of clusters and clusters in WT and in CCR5 -/-CD4 + T cells, we used a Bayesian inference model on top of a mechanistic model (Castro et al, 2014). The model assumes that TCR aggregates by incorporating one receptor at a time, with on and off rates that depend on the diffusion properties of the receptor on the membrane, but not existing cluster size.…”
Section: Mathematical and Bayesian Analysesmentioning
confidence: 99%
“…These epitopes are expected to bind MHC molecules on the surface of antigen-presenting cells (APCs) and hence be directly presented to T cells. [143][144][145] In addition, a few clinical teams tested the therapeutic profile of fulllength TAAs, 146 "synthetic long peptides" (SLPs), i.e., TAA-derived peptides of 25-35 amino acids; [147][148][149][150] or "carbohydrate-mimetic peptides" (CMPs), i.e., synthetic polypeptides that mimic the structure of carbohydrate TAAs. 151 The use of SLPs as therapeutic anticancer vaccines presents several advantages as compared to that of short TAA-derived peptides.…”
Section: Literature Updatementioning
confidence: 99%